STUDI KELAYAKAN MEDIA PEMBELAJARAN SYAIR AGAMA “PERAHU” KARYA HAMZAH FANSURI DALAM PENANAMAN PENDIDIKAN MORAL - Silvia Sandi Wisuda Lubis (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Abstract: Feasibility Study of Religious Poetry Learning Media "Boat" by Hamzah Fansuri in Planting Moral Education. The development of science and technology increasingly encourages renewal efforts in the use of technological results in the teaching and learning process or referred to as the media. If the media carries messages or information that aims to be instructional or contain teaching purposes, then the media is called learning media. The poem is essentially an old literature that can also be written down and must be preserved. Poetry is very tangent to religious and moral teachings. The data analysis technique uses interview data collection and documentation. The results of interview data collection by Indonesian lecturers were conducted to determine the feasibility of the "Boat" poetry learning media. The results of processing the processed data indicate that the poem "Boat" is suitable to be used as a learning medium in instilling moral education, namely with the eligibility criteria ≤ 51% (worth it).Keywords : Learning Media, Poetry, Moral Education Abstrak : Studi Kelayakan Media Pembelajaran Syair Agama “Perahu” Karya Hamzah Fansuri Dalam Penanaman Pendidikan Moral. Perkembangan ilmu pengetahuan dan teknologi semakin mendorong upaya-upaya pembaharuan dalam pemanfaatan hasil-hasil teknologi dalam proses belajar mengajar atau disebut dengan media.  Apabila media itu membawa pesan-pesan atau informasi yang bertujuan instruksional atau mengandung maksud-maksud pengajaran maka media itu disebut media pembelajaran. Syair hakikatnya merupakan salah satu sastra lama yang juga bisa  dilisankan dan harus dilestarikan. Syair sangat bersinggungan dengan ajaran agama dan moral. Teknik analisis datanya menggunakan pengumpulan data wawancara serta dokumentasi. Hasil pengumpulan data wawancara oleh dosen bahasa Indonesia dilakukan untuk mengetahui kelayakan media pembelajaran syair “Perahu”. Hasil pengolahan data yang diolah menunjukkan bahwa syair “Perahu” layak digunakan sebagai media pembelajaran dalam menanamkan pendidikan moral, yaitu dengan kriteria kelayakan ≤ 51% (layak).Kata Kunci : Media Pembelajaran, Syair, Pendidikan Moral